Engineering Olefin‐Linked Covalent Organic Frameworks for Photoenzymatic Reduction of CO2. Issue 12 (3rd February 2022) - Zhao, Zhengfeng; Zheng, Dong; Guo, Menglei; Yu, Jiangyue; Zhang, Sainan; Zhang, Zhenjie; Chen, Yao
Abstract: It is of profound significance concerning the global energy and environmental crisis to develop new techniques that can reduce and convert CO2 . To address this challenge, we built a new type of artificial photoenzymatic system for CO2 reduction, using a rationally designed mesoporous olefin‐linked covalent organic framework (COF) as the porous solid carrier for co‐immobilizing formate dehydrogenase (FDH) and Rh‐based electron mediator. By adjusting the incorporating content of the Rh electronic mediator, which facilitates the regeneration of nicotinamide cofactor (NADH) from NAD +, the apparent quantum yield can reach as high as 9.17±0.44 %, surpassing all reported NADH‐regenerated photocatalysts constructed by crystalline framework materials. Finally, the assembled photocatalyst–enzyme coupled system can selectively convert CO2 to formic acid with high efficiency and good reusability. This work demonstrates the first example using COFs to immobilize enzymes for artificial photosynthesis systems that utilize solar energy to produce value‐added chemicals. Abstract : A new photocatalyst–enzyme coupled artificial photosynthesis system was constructed for photoenzymatic reduction of CO2 using COFs as enzyme carriers. The hybrid system showed an apparent quantum yield as high as 9.17±0.44 %, surpassing the reported NADH‐regenerated photocatalysts of crystalline framework materials.